Recombinant humanized collagen combined with nicotinamide increases the expression level of rat basement membrane proteins and promotes hair growth - Zhou, Youshiqi; Chen, Boyu; Ye, Shijia; Sun, Haoyu; Wang, Shuyue; Diao, Xiaozhen; Wu, Wenhui (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundHair follicle stem cells (HFSCs) play crucial roles in hair growth and are expected to be potential targets in regenerative medicine and tissue engineering.MethodThis study aims to investigate the positive effect on hair growth by the recombinant human collagen complex (RHC complex), composed of rhCOL III, rhCOL XVII, and rhCOL XXI, along with nicotinamide, both in vitro and in vivo, by HFSCs and rat models. The survival rate, function, and differentiation of HFSCs were investigated.ResultsThe CCK-8 experiment showed that the RHC complex was non-toxic to HFSCs, and the cell survival rate exceeded 80% after 8 and 16 h of treatment. The ELISA method showed that the RHC complex significantly increased the intracellular vascular endothelial growth factor (VEGF) levels. In addition, the increase in the content of trichohyalin (a key structural protein of hair) indicates that the structure and function of hair follicles may be enhanced. The expression levels of β-integrin and p63 were significantly upregulated, which are crucial for cell adhesion, migration, and maintenance of HFSCs homeostasis. In the rat model, significant hair growth was observed after a 7-day treatment period. The period of vigorous hair growth in rats was selected for immunofluorescence, enzyme-linked immunosorbent assay (ELISA) and hematoxylin-eosin (HE) staining analysis. The results showed that the RHC complex could promote the expression of Integrin, Laminin and Perlecan, which were conducive to maintaining the stability of the microenvironment of HFSCs. Additionally it facilitated the migration and differentiation of HFSCs, as evidenced by an increased number of hair follicles in HE-stained skin tissues. In conclusion, the RHC complex exhibited high HFSCs survival rates and enhanced the expression of HFSCs-associated factors and basement membrane proteins. These properties make the RHC complex a promising novel ingredient for promoting hair growth, preventing hair loss, and maintaining hair health.